2020
DOI: 10.3390/agronomy10081177
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Multiple Planting Densities on Lignin Metabolism and Lodging Resistance of the Strip Intercropped Soybean Stem

Abstract: The shading of maize and self-shading are the key factors affecting the stem lignin biosynthesis and lodging resistance of soybean at middle and later growth stages in the strip intercropping system. A study was designed to explore the regulation mechanism of lignin metabolism and different planting densities; PD1, PD2, and PD3 were used having a total number of 17 plants m−2, 20 plants m−2, and 25 plants m−2, respectively, on the lodging resistance of strip intercropped soybean stem. Our results depicted that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
35
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(38 citation statements)
references
References 76 publications
3
35
0
Order By: Relevance
“…Most specifically, the plant height was decreased by 6.2% and 9.4% at 17 and 20 plants/m 2 , respectively than that of 25 plants/m 2 planting density. In addition, decreasing the planting densities such as 17 and 20 plants/m 2 could decrease the lodging percentage by 50.3% and 19.3%, respectively as compared to 25 plants/m 2 planting density [ 134 ]. However, further field experiments to optimize the planting densities in the maize-soybean intercropping system Table 2 .…”
Section: Agro-techniques For the Management Of Lodging Stressmentioning
confidence: 99%
“…Most specifically, the plant height was decreased by 6.2% and 9.4% at 17 and 20 plants/m 2 , respectively than that of 25 plants/m 2 planting density. In addition, decreasing the planting densities such as 17 and 20 plants/m 2 could decrease the lodging percentage by 50.3% and 19.3%, respectively as compared to 25 plants/m 2 planting density [ 134 ]. However, further field experiments to optimize the planting densities in the maize-soybean intercropping system Table 2 .…”
Section: Agro-techniques For the Management Of Lodging Stressmentioning
confidence: 99%
“…These soybean-related restrictions are obviously linked to maize canopy development (Chui and Shibles, 1984;Liu et al, 2017a). In addition, maize shade affects the stem circumference of soybean and lowers its lodging susceptibility (Liu et al, 2016;Raza et al, 2019a;Cheng et al, 2020). Low PAR and the ratio of red light to far red light, which decreased because of the maize canopy, also produce soybean stem vining in maize-soybean relay strip intercropping.…”
Section: Effect On Plantsmentioning
confidence: 99%
“…Hussain et al [8] argued that shading reduces the amount of lignin deposited in the cells of vascular bundles and sclerenchyma, rendering the stems slender and more fragile. Cheng et al [9] showed that when soybeans were intercropped, decreasing their planting density could increase the activity of lignin-related enzymes and the accumulation of carbohydrates, thereby enhancing the lodging resistance of soybean stems.…”
Section: Introductionmentioning
confidence: 99%